CD36 Shunts Eicosanoid Metabolism to Repress CD14 Licensed Interleukin-1β Release and Inflammation - Zoccal, Karina F.; Gardinassi, Luiz G.; Sorgi, Carlos A.; Meirelles, Alyne F. G.; Bordon, Karla C. F.; Glezer, Isaias; Cupo, Palmira; Matsuno, Alessandra K.; Bollela, Valdes R.; Arantes, Eliane C.; Guimarães, Francisco S.; Faccioli, Lúcia Helena (Frontiers in Immunology, 2018)
Interleukin (IL)-1β is a potential target for treatment of several inflammatory diseases, including envenomation by the scorpion Tityus serrulatus. In this context, bioactive lipids such as prostaglandin (PG) E2 and leukotriene (LT) B4 modulate the production of IL-1β by innate immune cells. Pattern recognition receptors (PRRs) that perceive T. serrulatus venom (TsV), and orchestrate LTB4, PGE2, and cyclic adenosine monophosphate (cAMP) production to regulate IL-1β release are unknown. Furthermore, molecular mechanisms driving human cell responses to TsV remain uncharacterized. Here, we identified that both CD14 and CD36 control the synthesis of bioactive lipids, inflammatory cytokines and mortality mediated by TsV. CD14 induces PGE2/cAMP/IL-1β release and inflammation. In contrast, CD36 shunts eicosanoid metabolism towards production of LTB4, which represses the PGE2/cAMP/IL-1β axis and mortality. Of importance, the molecular mechanisms observed in mice strongly correlate with those of human cell responses to TsV. Overall, this study provides major insights into molecular mechanisms connecting CD14 and CD36 with differential eicosanoid metabolism and inflammation mediated by IL-1β.